GC–MS evaluation of Cymbopogon citratus (DC) Stapf oil obtained using modified hydrodistillation and microwave extraction methods - Ajayi, E.O.; Sadimenko, A.P.; Afolayan, A.J. (Food chemistry, 2016)
•Bioactive compounds of Cymbopogon citratus oils were identified.•Analyses of the oils revealed 7, 16, 22, and 15 compounds in the various media respectively.•Total yield of volatile fractions was 0.73%, 0.64%, 0.70%, and 0.45% in different media respectively.•Citral was found to be the major component and was found to be highest in the base-distilled medium.•High molecular alkanes were obtained specially by the microwave method. Bioactive compounds of Cymbopogon citratus essential oil, using different media have been tentatively identified with the aid of gas chromatography–mass spectrometry (GC–MS). Hydrodistillation was complemented using weakly acidic and alkaline media for the oil extraction. Solvent-free microwave extraction (SFME) was also used. Analyses of the oils revealed the presence of 7, 16, 22, and 15 compounds in the water-distilled (WD), microwave-distilled (MD), acid-distilled (AD), and base-distilled (BD), essential oils, respectively. Total yield of the volatile fractions was 0.73%, 0.64%, 0.70%, and 0.45%, respectively. Citral was found to be the major component, the base extraction having the highest content. This was followed by 2-isopropenyl-5-methylhex-4-enal, p-cymene, and 2-thujene. The antimicrobial, antibacterial, and antioxidant activities and assessment of medicinal/nutritional uses of the essential oils are subjects of future studies.